Meningkatkan Kepuasan Pengguna Layanan Publik melalui Fasilitas dengan Kualitas Layanan sebagai Variabel Interverning - Ardiasih, Avita Putri; Cahyoadi, Bayu (Jurnal Pendidikan Ekonomi Undiksha, 2024)
in a public agency. The purpose of this study was to determine the effect of facilities on public service user satisfaction, to determine the effect of facilities on public service quality, and to determine the effect of service quality on public service user satisfaction. Data collection using a questionnaire with a total of 200 respondents. This research uses structural equation modeling (SEM) with AMOS 26.0 software. The results of SEM data processing fulfill the goodness of fit as follows: chi square value = 80.994; CMIN/DF = 1.306; probability = 0.053; GFI = 0.941; AGFI = 0.914; TLI = 0.976; CFI = 0.981; RMSEA = 0.039. The results of data processing conclude that there is an influence between facility variables on public service user satisfaction with a probability of 0.000 below the p-value of 0.05; there is an influence of facility variables on service quality with a probability of 0.000 below the p-value of 0.05; there is an influence of service quality variables on public service user satisfaction with a probability of 0.000 below the p-value of 0.05.